Exploring hydrotourism: Health and wellbeing - Ernawati, Ni Made; Mudana, I Gede; Sari, Putu Yunita Wacana; Indrawati, Yayu; Pamularsih, Tyas Raharjeng (Journal of Commerce, Management, and Tourism Studies, 2025)
This emic study presents literature research of qualitative study on hydrotourism - health and wellness focusing on the practices and the uniqueness of the product offering around the globe highlighted with hydrotourism - health and wellness offered in Bali Indonesia. The findings show hydrotourism as a generic name represents three types of leisure and tourism products: water for sport, health and wellness, and for panoramic viewing experience. The current well developed and highly innovative products of hydrotourism - health and wellness around the world which could create a strong allegiance to particular destinations, has been known since the nomadic era. Bali offers high quality and variety of spa products that often offered by hotels or independents spa–establishment; it is noted that hydro for spiritual purification of ‘melukat-ritual’ is highly popular among tourists and become a substantial hydro product offer which is rooted from Hindu practice. Hydrotourism - health and wellness offer high variety and each with unique selling proposition. Hydrotourism – health and wellness could be in the form of bathing, spiritual purification, healing and rejuvenation, medication to relieve pain, detoxification and skin beauty, and a more complex spiritual ceremony of forging the endurance of body and mind; during the process, it could utilize various materials to assist healing, e.g. stone and herbs, or leveraging extreme temperature of warm and cold, often combined with yoga practice and meditation, also consuming healthy and whole food during the program; it could be an exclusive and luxurious for the rich, spa and wellness products for travelers, or simply public bathing where children and people could go to refresh; it could be well facilitated spa establishments with prime service or simply public baths, natural spring and thermal baths managed by local community. Indonesia considers spa services as traditional health services rather than entertainment.